ANALISIS PEMBELAJARAN NAHWU MENGGUNAKAN KITAB MATAN AL-JURUMIYAH PADA KELAS PEMULA DI PONDOK PESANTREN RAHMATUL UMMAH AS-SALAFIYYAH AN-NAHDHIYYAH - Roslina, Dina; Iqbal Hs, Ahmad; Bukhari Muslim, Ahmad; Afif Amrulloh, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the nahwu learning process through the use of the Matan al-Jurumiyah book among second-grade ibtida’ students, who are beginners in nahwu studies. The research was conducted at Pondok Pesantren Rahmatul Ummah As-Salafiyyah An-Nahdhiyyah, Fajar Baru, South Lampung, using a descriptive qualitative approach. Data were collected through interviews, observations, and documentation. The findings reveal that Matan al-Jurumiyah effectively supports students’ understanding of basic nahwu concepts due to its concise, systematic, and easily memorized content. The effectiveness of learning is also influenced by the teacher’s ability to combine classical and modern teaching approaches. The teacher applies an inductive (istiqra’iyyah) method and various learning strategies, including mudzakarah, mentarkib (sentence structure analysis), hifẓ al-mutun, and question-and-answer sessions to facilitate memorization and comprehension. In addition, educational games (game-based learning) are integrated to increase students’ learning motivation, create a more engaging classroom atmosphere, and reduce anxiety toward nahwu, which is often considered difficult. However, some students still face challenges, particularly in memorizing and understanding certain materials such as the chapter on ‘Alamat al-I‘rab, due to similar and confusing sentence structures. Overall, this study highlights the essential role of the teacher as a facilitator who promotes collaboration, creativity, and adaptability to students’ abilities, resulting in a more effective and conducive learning process for basic nahwu instruction.